Status of Karnal bunt disease of wheat in Punjab (1994- 2004) - H. SINGH; R.C. SHARMA, INDU SHARMA, G.S. NANDA (Indian Phytopathology, 2004)
An effort has been made to highlight the status of different grain markets of Punjab state with regards to Karnal bunt (KB). Less affected areas during the last 11 years ( 1994-2004) from where wheat may be procured for export either by segregation at the grain market level or by contract farming are identified. Year to year variations occur in the disease as is evident from the percent KB - free samples recorded in different years. Amongst different districts, the disease was least in Patiala where av. KB – free samples were 85 % followed by samples from Amritsar (81.12%). Av. KB-free samples were as high as 90 % and above in seven grain markets in Punjab (Amritsar, Kotshmeer, Bagharian, Delhon, Muktsar, Bhadson and Bhasor).